2015
DOI: 10.1097/nnr.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Self-Management in Chronic Care

Abstract: A nurse's perception of self-management substantially impacted how care was individualized. Patient assessment was the key driver of tailoring, which was performed in various ways, and influenced how and the extent to which care was individualized. To enable responding to the unique wishes and needs of individual patients, both scientific and educational efforts need to be directed toward systematic assessments of patient capacity to self-manage their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…TPE programs can lead to changes in HPs’ attitudes,33,59,60 and several studies have suggested that this attitude change helps strengthen HPs’ self-management/TPE practices 18,61. In this context, educative attitude is a key resource in educational competency and TPE practices and should be included in TPE recommendations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPE programs can lead to changes in HPs’ attitudes,33,59,60 and several studies have suggested that this attitude change helps strengthen HPs’ self-management/TPE practices 18,61. In this context, educative attitude is a key resource in educational competency and TPE practices and should be included in TPE recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…The patients identified the need for their HP to recognize their (the patients’) expertise and skills, to see them as a whole person rather than just a disease, to share information with them and to prioritize quality of life. Bos-Touwen et al18 demonstrated the importance of recognizing patients’ ability to take care of themselves as a factor affecting self-care practices and nurses’ overall assessment of patients. Norris and Kilbride19 pointed out the perceived challenge that patient empowerment and the loss of control inherent in that type of approach poses to HPs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that participants vary in their attitude, needs and preferences towards self‐management support, personalized support after kidney transplantation is necessary (Grijpma et al., ). To enable nurses to respond to recipient's unique educational needs, they must assess recipient's knowledge, information needs and desired methods of education (Bos‐Touwen et al., ). Providing standard education alone will not lead to behavioural change and is not sufficient for improving recipients’ self‐management skills (Barlow, Cooke, Mulligan, Beck, & Newman, ; Coster & Norman, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the consultations, nurses continuously multitasked and rapidly shifted between medical examinations and health topics according to the health care standards, without leaving room for an in-depth focus on patients' perspectives and selfmanagement topics. Other studies have found that the decision to address selfmanagement topics and induce behaviour change is influenced by the variety in nurses' perceptions of their roles, tasks, and responsibilities of self-management (Been-Dahmen et al, 2015;Bos Touwen et al, 2015;Morgan et al, 2017) and a lack of consultation time (Jansink, Braspenning, van der Weijden, Elwyn, & Grol, 2010;Lawn & Schoo, 2010;Taylor, Shaw, Dale, & French, 2011).…”
Section: Continuedmentioning
confidence: 99%